Transaksi Digital dan Aset Kripto dalam Tinjauan Fikih Muamalah Kontemporer - Khaerunnisa Wahid; Nurul Fatimah; Achmad Musyahid Idrus; M. Tahir Maloko (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid advancement of digital technology has transformed global financial systems and introduced new instruments such as cryptocurrencies, which have attracted widespread attention in modern society. This article, titled “Digital Transactions and Cryptocurrency in the Perspective of Contemporary Fiqh al-Muamalah,” aims to analyze the legal status, ethical dimensions, and socio-economic implications of digital assets within the framework of Islamic jurisprudence. The study employs a qualitative-descriptive approach, drawing upon classical and contemporary fiqh sources, scholarly fatwas, and modern Islamic financial regulations. The findings indicate that digital transactions, including cryptocurrency usage, are permissible (mubah) under Islamic law, provided they fulfill the principles of Islamic muamalah—namely contractual clarity (al-aqd al-sarih), justice (al-adl), and avoidance of gharar (uncertainty), riba (usury), and maisir (gambling). Cryptocurrencies may be recognized as a legitimate form of investment and medium of exchange when their intrinsic value, transparency, and purpose align with Shariah principles. However, the volatility of value and potential misuse in illicit transactions necessitate strong Shariah oversight and state regulation. Therefore, from the standpoint of contemporary fiqh al-muamalah, cryptocurrencies can be classified as mal istibdali (substitutable assets), permissible under Shariah when they serve public benefit (maslahah ammah) and uphold ethical financial practices.